Invisible giants in broadcast journalism: news agencies and the global news ecosystem - Esperidião, Maria Cleidejane (Brazilian journalism research, 2011)
Key actors of the global informational web, the international television news agencies are not often covered in the communications field in Brazil. This paper aims to understand the dynamics established between these transnational companies and their subscribers (world television stations). It attempts to clarify how these western-led news agency companies operate within the flow of communication. It intends to identify production processes (assessment, collection, treatment and radial distribution) for the Associated Press Television News (APTN) and Reuters Television News (Reuters TV).